2015
DOI: 10.2147/cia.s89127
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome in octogenarians: association between percutaneous coronary intervention and long-term mortality

Abstract: AimEvidence of improved survival after use of percutaneous coronary intervention (PCI) in elderly patients with acute coronary syndrome (ACS) is limited. We assessed the association between PCI and long-term mortality in octogenarians with ACS.Methods and resultsWe followed 353 consecutive patients aged ≥80 years hospitalized with ACS during 2006–2007. Among them, 182 were treated with PCI, whereas 171 were not. PCI-treated patients were younger and more often male, and had less stroke and dependency in activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Moreover, a systematic review of clinical studies performed to identify the health-related quality of life (HRQOL) after PCI in the elderly, showed that they have significant improvements in cardiovascular well-being after PCI [ 20 ]. Another recent study conducted in octogenarians, also exhibited the benefits of PCI in a cohort of 353 consecutive patients with ACS [ 21 ]. In overall cohort, 5-years all-cause mortality was 46.2% vs 89.5% comparing PCI and non-PCI groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a systematic review of clinical studies performed to identify the health-related quality of life (HRQOL) after PCI in the elderly, showed that they have significant improvements in cardiovascular well-being after PCI [ 20 ]. Another recent study conducted in octogenarians, also exhibited the benefits of PCI in a cohort of 353 consecutive patients with ACS [ 21 ]. In overall cohort, 5-years all-cause mortality was 46.2% vs 89.5% comparing PCI and non-PCI groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a statistically significant association between PCI and reduced long-term mortality was found. Furthermore, a significant improved mean survival rates was observed for PCI-treated patients [ 21 ]. All these consistent data, together with the result of the Cox univariate and multivariate analysis performed in the present study, confirm that performing catheterization and revascularization have better outcomes than conservative medical therapy in elderly presenting ACS.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated phi ( as a measure of effect size, with values of ∼0.1, ∼0.3, and ≥0.5 roughly corresponding to small, medium, and large effects, respectively. 71 For experiment 2, we compared cricket mortality among the four C60 dosage groups using a Kaplan-Meier survival model, 75 which included both a dichotomous dependent variable (survival within 60 hr) and a continuous dependent variable (hours of survival, at the five time intervals). Because the two trials yielded identical conclusions, we combined them for analysis and presentation.…”
Section: Analysesmentioning
confidence: 99%
“…Because the two trials yielded identical conclusions, we combined them for analysis and presentation. We used the Mantel-Cox log-rank method 75 for multiple comparisons among C60 dosage groups. We calculated as an effect size for survival at 60 hr by comparing the proportion of crickets that survived in the 0 g/g control group …”
Section: Analysesmentioning
confidence: 99%
“…28 Most data come from large registry data sets. 29,30 In initial trials published including data from the Non-ST-Segment Elevation -ACS (NSTE-ACS) European registry, roughly a third (27-34 %) of patients are aged ≥75 years, but this proportion has dropped to no more than 20 % of all patients in recent trials. Even when older patients are recruited into clinical trials, they are highly selected, often having substantially less comorbidity than patients encountered in daily clinical practice.…”
Section: Non-st Segment Myocardial Infarctionmentioning
confidence: 99%